Capitalisation of the Media Industry From a Political Economy Perspective - Manfred Knoche (tripleC: Communication, Capitalism & Critique)
Approaches to the critique of the political economy of communication in society belong to the “forgotten theories” in media and communication studies. But in view of the unmistakable structural change of a media industry “unleashed” by deregulation, privatisation, digitalisation, concentration, globalisation, etc., it seems from an academic perspective necessary to analyse the development of the media industry in close connection with the equally unmistakable general development of an “unleashed” capitalism. This article therefore shows that the analysis of the development processes of capitalism as the undoubtedly globally dominant economic and social system from a political economy perspective makes it possible to analyse, explain, and partly forecast the economisation or commercialisation process in the media industry in an academically appropriate way with regard to its causes, forms, consequences, and further development. Theoretical explanations are offered by the further developments of the analysis and critique of contemporary capitalism based on Marx’s critique of the political economy as a historical-materialist analysis of society. In doing so, the permanent fundamental characteristics, modes of functioning and “regularities” of the capitalist mode of production and the capitalist formation of society are analysed in connection with the particularities of the current capitalisation process in the media industry.